2015
DOI: 10.1177/0003319715592095
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications Following Transradial and Transulnar Coronary Angiography in 1600 Consecutive Patients

Abstract: Although infrequent, surveillance for major complications should be encouraged after forearm coronary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
2
14
0
3
Order By: Relevance
“…, Panels D–F). As it has been reported, incidence of compartment syndrome is a very low following transradial coronary intervention . To our knowledge, this is the first case report of severe dorsal hand laceration secondary to compartment syndrome.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…, Panels D–F). As it has been reported, incidence of compartment syndrome is a very low following transradial coronary intervention . To our knowledge, this is the first case report of severe dorsal hand laceration secondary to compartment syndrome.…”
supporting
confidence: 49%
“…As it has been reported, incidence of compartment syndrome is a very low following transradial coronary intervention. 1,2 To our knowledge, this is the first case report of severe dorsal hand laceration secondary to compartment syndrome. A high suspicion with any complaint of pain and swelling in the forearm and a proper management of hemostasis with great emphasis in high-risk population, especially elderly, female patients with low body surface area are the key points.…”
mentioning
confidence: 80%
“…Moreover, the radial approach is also associated with more comfort for the patient, shorter hospitalization stays, and lower costs of treatment. However, RAO is one of the major complications of procedures performed via the radial artery [17,18]. Although with an asymptomatic course, as well as the incidence of hand ischemia caused by RAO is extremely rare, RAO eliminates the ability to use the radial artery as an access for PCI in the future, to use it as a bypass conduit for patients undergoing coronary artery bypass surgery, or to use it for dialysis fistula.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In transulnar catheterization, investigators in a small single-center prospective study showed a low incidence of vascular sequelae, in which 2 patients (0.4%) had developed major forearm hematomas that resolved without clinical consequences. 10 In a large prospective study of more than 10,000 patients, the overall vascular sequela rate in transradial percutaneous coronary procedures was 0.5%, and there were 2 cases of compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%